Political Potentials, Deep-Seated Nativism and the Success of the German AfD - Schulte-Cloos, Julia (Frontiers in Political Science, 2022)
The German populist radical right party “Alternative for Germany” (AfD) was founded amid various economic and political crises. This article argues that the electoral success of this political challenger, however, is rooted in more than the upsurge of populist resentments born out of these crises. Integrating theories about the activation of attitudes with arguments about the effects of exposure to local political contexts, I contend that the electoral success of the AfD reflects the mobilization of deep-seated nativist sentiments. To test these propositions, I draw on a large panel dataset of the AfD’s electoral returns at the municipal level (N = 10,694) which I link to pre-crises data on the marginal success of extreme-right parties. Exploiting variation between municipalities located within the same county (N = 294), I estimate a series of spatial simultaneous autoregressive error models by maximum likelihood estimation. The results show that the success of the AfD is rooted in the local prevalence of nativist sentiments that date prior to the crises that fomented the formation of the challenger party–an effect that becomes stronger in the course of the radicalization of the AfD. I further demonstrate that the populist right AfD is best able to broaden its electoral appeal among local communities with an extreme-right sub-culture, particularly in Eastern Germany. This suggests that even small extreme-right networks can act as a breeding ground for the populist right and help spread xenophobic and nativist sentiments among citizens.